Prediction of Optimum Hydrate Inhibitors Mass Percent for Hydrate Formation Prevention - Kinate, Bright Bariakpoa; Igwe, Ikechi; Elikee, Uchenna Daniel (Journal of Earth Energy Science, Engineering, and Technology, 2023)
The production tubing and pipeline have the critical task of transporting economically significant fluids.  As a result, they must be meticulously designed to manage potential issues like gas hydrate formation that can lead to blockage of the pipeline. In this study, the OLGA dynamic multiphase simulator and Multiflash were employed to determine the optimum mass percentages of thermodynamic inhibitors- namely, methanol, monoethylene glycol (MEG), diethylene glycol (DEG) and triethylene glycol (TEG) that are necessary to prevent hydrate formation within the pipeline. The pipeline model was developed using OLGA and Multiflash to characterised the fluid properties and generate the requisite input files (hydrate and PVT table files) for dynamic multiphase simulation with OLGA. Sensitivity analyses were performed to determine the optimum mass percent of methanol, MEG, DEG, and TEG required to suppress hydrate formation in the pipeline. Different mass percent of 10%, 20% 30%, 40%, 50%, 60%, 70%, 80% and 90% of the four inhibitors were introduced into the pipeline to evaluate their impact on hydrate volume fractions and locations along the pipeline at where hydrate attains thermodynamic stability. Addition of the inhibitors was stopped when the system exhibited conditions of no hydrate volume fraction. Result shows that the optimum mass percent for complete hydrate inhibition was 60% for methanol, 45% for MEG, and 70% for TEG inhibitors in the pipeline. DEG showed reduced hydrate fraction but did not inhibit formation effectively even at 90%. It was observed that as the inhibitor mass percent increases, the hydrate dissociation temperature (the temperature below which the hydrate will form) is reduced for a given pressure. Consequently, Monoethylene glycol (MEG) with an optimal mass percentage of 45% was the most efficient inhibitor for curbing hydrate formation within the given pipeline, surpassing the performance of other inhibitors and offering potential cost saving.